Coach strategies for fostering positive youth development through sports - Erdilanita, Ulma; Ma'mun, Amung; Berliana, Berliana (Universitas Tanjungpura, 2025)
Background. Adolescence is a crucial stage of development that significantly influences future well-being. Sport participation has been shown to support positive youth development by enhancing physical health, life skills, and self-esteem. Coaches play a vital role in creating supportive sport environments that foster holistic growth. Objectives. The purpose of this research was to identify and review strategies used by coaches to encourage positive youth development through sport. Methods. The method used is a literature review. Together with colleagues, articles were sorted through the Taylor & Francis database. A review was carried out on articles from 2020 to 2024 using the PRISMA flowchart for selection and extraction. Data search was carried out using the keywords